Copulation Exerts Significant Effects on mRNA Expression of Cryptochrome Genes in a Moth. Issue 2 (28th February 2019) - Xu, Jin; Gao, Bo; Shi, Min-Rui; Yu, Hong; Huang, Ling-Yan; Chen, Peng; Li, Yong-He
Abstract: It is recognized that the behavioral rhythms of organisms are controlled by the circadian clock, while the reverse direction, i.e., whether changes in physiology and behavior react to the internal rhythms, is unclear. Cryptochromes (CRYs) are photolyase-like flavoproteins with blue-light receptor function and other functions on circadian clock and migration in animals. Here, we cloned the full-length cDNA of CRY1 and CRY2 in Spodoptera litura (Fabricius, 1775) (Lepidoptera: Noctuidae). Sl -CRYs show high similarity to orthologs from other insects, and their conserved regions contain a DNA photolyase domain and a FAD-binding seven domain. The expression levels of both genes were relatively low during the larval stage, which increased during the pupal stage and then peaked at the adult stage. The expression of Sl-CRY1 and Sl-CRY2 showed differences between males and females and between scotophase and photophase. Further, our study demonstrated that copulation has a significant effect on the expression of Sl-CRYs . More interestingly, the changes in the expression of Sl-CRY1 and Sl-CRY2 due to copulation showed the same trend in both sexes, in which the expression levels of both genes in copulated males and females decreased in the subsequent scotophase after copulation and then increased significantly in the following photophase. Considering the nature of the dramatic changes in reproductive behavior and physiology after copulation in S. litura, we propose that the changes in the expression of Sl-CRYs after copulation could have some function in the reproductive process.